2016
DOI: 10.1186/s13098-016-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Is vaspin related to cardio-metabolic status and autonomic function in early stages of glucose intolerance and in metabolic syndrome?

Abstract: BackgroundThis study aims to assess serum vaspin in early stages of glucose intolerance and in the presence of metabolic syndrome (MetS); and to evaluate vaspin correlation to different cardio-metabolic parameters and autonomic tone in these subjects.Methods185 subjects (80 males and 105 females) of mean age 45.8 ± 11.6 years and mean BMI 31.2 ± 6.3 kg/m2, divided into groups according to: glucose tolerance, presence of MetS and cardio-vascular autonomic dysfunction (CAD), were enrolled. Glucose tolerance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 17 Other studies found that vaspin level increased with aging and was associated with parasympathetic activity even in the absence of metabolic syndrome. 18 In addition, a study found that vaspin cannot be used as an independent marker for the presence of coronary artery disease in the general population. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 17 Other studies found that vaspin level increased with aging and was associated with parasympathetic activity even in the absence of metabolic syndrome. 18 In addition, a study found that vaspin cannot be used as an independent marker for the presence of coronary artery disease in the general population. 19 …”
Section: Discussionmentioning
confidence: 99%
“…An interesting observation was demonstrated in the independent research of Ataya et al and Feng et al Considering the duration of diabetes, the negative correlation between time and vaspin concentration was shown [48,59]. Based on these results, Dimova et al suggested that vaspin plays a compensative role in glucose metabolism disorders at the outset of type 2 diabetes (T2DM), and its secretion capacity gradually declines with the increase of the diabetes duration [60]. However, the results of studies conducted on humans are ambiguous.…”
Section: Adipokinesmentioning
confidence: 92%
“…There were significant associations of high vaspin levels with glucose and lipid-related metabolic parameters in severely obese patients, as well as post-operative increases in vaspin levels, and correlations of higher pre-and postoperative vaspin concentrations with better metabolic profile [81]. Studies carried out on the Caucasian population demonstrate no overt fluctuations in vaspin levels in the early stages of glucose intolerance and MetS [60]. Opposing results were previously reported by Kim et al The authors demonstrated that serum vaspin concentration was significantly lower in men with MetS than in men without MetS.…”
Section: Adipokinesmentioning
confidence: 92%
“…Vaspin is a visceral adipose tissue-derived serine protease inhibitor with insulin-sensitizing effects associated with IR. Circulating vaspin levels increased with aging and were associated with parasympathetic activity even in the absence of metabolic syndrome [124]. Frail older adults showed higher levels of vaspin compared to participants who did not show frailty [125].…”
Section: Endocrine Dysregulationmentioning
confidence: 98%